Detailed stratigraphy of Kansas coals. A review of Erasmus Haworth's report on Kansas coals, 1898 - Christensen, Frederic Waldemar (My University, 1900)
Introduction: The Kansas coals occur in various shales and all positions, from the Cherokee shales at the base to the Osage shales, 2000 feet above. The order and position of the strata is shown in the generalized section figure. The Cherokee shales produce greater quantities of coal than any other shale beds in the whole Coal Measures. From these shales, are obtained the coals of Cherokee and Crawford Counties and nearly all of Labette and Leavenworth Counties. Borings, as of wells, show that the Cherokee shales extend over a considerable area west, and the probability is that coal can be found anywhere under the eastern fifty or seventy five miles of the state. The Labette shales, first in order above the Cherokee shales, contain considerable bituminous matter, but no good bed coal. Above this, we have the Pleasanton shales, which contain large quantities of coal, especially in the lower Pleasanton shales. They probably rank next to the Cherokee shales. The Thayer shales carry a considerable amount of coal, especially in the vicinity of Thayer. The Lane shales, next in importance, have no coal as far as is known. Above this are the Lawrence shales, which produce coal enough to be of commercial importance. In Atchison, Jefferson, Douglas, and Franklin counties, coal is mined from these shales. Above the Lawrence shales, the shale beds contain little or no coal, until the Osage shales are reached. The average thickness of this formation is about 200 feet. It extends across the state, from the north to the south. It is rich in coal, and is extensively mined at Burlingame, Osage City, Carbondale, and Scranton. The quantity and quality varies considerably in different sections.
Citation: Christensen, Frederic Waldemar. Detailed stratigraphy of Kansas coals. A review of Erasmus Haworth's report on Kansas coals, 1898. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Geology; Coal; Shale; Kansas; Theses